A lipid gating mechanism for the channel-forming O antigen ABC transporter - Caffalette, C; Corey, R; Sansom, M; Stansfeld, P; Zimmer, J (Springer Nature, 2019)
Extracellular glycan biosynthesis is a widespread microbial protection mechanism. In Gram-negative bacteria, the O antigen polysaccharide represents the variable region of outer membrane lipopolysaccharides. Fully assembled lipid-linked O antigens are translocated across the inner membrane by the WzmWzt ABC transporter for ligation to the lipopolysaccharide core, with the transporter forming a continuous transmembrane channel in a nucleotide-free state. Here, we report its structure in an ATP-bound conformation. Large structural changes within the nucleotide-binding and transmembrane regions push conserved hydrophobic residues at the substrate entry site towards the periplasm and provide a model for polysaccharide translocation. With ATP bound, the transporter forms a large transmembrane channel with openings toward the membrane and periplasm. The channel’s periplasmic exit is sealed by detergent molecules that block solvent permeation. Molecular dynamics simulation data suggest that, in a biological membrane, lipid molecules occupy this periplasmic exit and prevent water flux in the transporter’s resting state.